'Death' Rarely Used in Family Discussions About Critically Ill Infants. Issue 1 (January 2023) - Rosenberg, Karen
Abstract : According to this study: In family meetings between clinicians and the parents of critically ill infants, medical jargon and other types of euphemisms are used more often than the words die, death, dying, or stillborn .